Membrane mutation affecting energy-linked functions in Escherichia coli K 12 - Braná, H; Hubácek, J; Michaljanicová, D; Holubová, I; Cejka, K (Folia microbiologica, 1977)
A small-colony forming variant of Escherichia coli with a mutation in the ncf gene was analysed. The alternation of the protein composition in the cytoplasmic membrane and the interaction with K and E group colicins indicated a membrane mutation. The effect of this mutation on some membrane-bound processes, the activity of Mg2+-activated ATPase, the growth on different carbon sources and the active transport of amino acids, is described. This mutation does not exert any effect on the electron transport system.
Keywords: membránové proteiny; Bacitracin; anaerobióza; glukosa; laktáty; Glucose; Membrane Proteins; geny; Cell Membrane; dodecylsíran sodný; kyselina deoxycholová; antibiotická rezistence; mutace; aerobióza; Aerobiosis; Genes; Vancomycin; Anaerobiosis; Bacterial Proteins; Colicins; koliciny; Escherichia coli; Mutation; Lactates; buněčná membrána; vankomycin; Adenosine Triphosphatases; Deoxycholic Acid; Amino Acids; Drug Resistance, Microbial; bakteriální proteiny; Sodium Dodecyl Sulfate; adenosintrifosfatasy; aminokyseliny; bacitracin